ТЕОРЕТИЧНІ АСПЕКТИ ХУДОЖНЬОГО ОБРАЗУ В МИСТЕЦТВІ (Педагогіка вищої та середньої школи, 2009)
In the present article considered the main qualities of artistic image, determined the problems which are stipul Annotation ated by definition of this term.